VULNERABILIDADE AO RISCO DE INUNDAÇÕES DA BACIA HIDROGRÁFICA DO BAIXO IGUAÇU POR MEIO DE GEOTECNOLOGIAS - Bortolini, Joseane (2022)
Geotechnologies, in general, have been proved to be valuable and useful tools in many different areas of expertise, as they allow, in addition to the collection and analysis of data, the recognition of realities linked to the area of interest. The main objective of this research was to contribute, with the usage of these technologies, with the mapping of information regarding the Baixo Iguaçu Hydrographic Unit (BIUH). Given its significant importance, there are still few papers linked to this field of study, which obtains even more prominence when aligned with the theme of areas vulnerable to occurrences such as floods. Therefore, it was carried out the delimitation and morphometric characterization of sub-basins within the Iguaçu River Basin, identifying, based on the morphometric analysis, the danger degree of floods and inundations of sub-basins linked to the BIUH (Paper 1). The usage of geotechnologies was applied for thematic mapping and structuring of the BIUH’s indicators database (Paper 2). Lastly, it was used the Analytic Hierarchy Process Method (AHP) associated with the GIS for the integrated mapping of vulnerability, the danger degree of floods and inundations was associated with the other criteria of exposure, susceptibility and adaptive capacity (Paper 3). There were 237 sub-basins that were morphometrically characterized, of which 95 comprise the BIUH. The operation of Remote Sensing (RS) and Geographic Information System (GIS) allowed mapping and structuring of the database with indicators that are relevant to the theme and even innovative for the field of study. The composite vulnerability mapping allowed the inference that the highest proportion of BIUH represented areas of medium vulnerability. However, by carrying out this study, it is expected to cooperate for the management of the BIUH, promoting information that, in addition to helping to mitigate the occurrence of the aforementioned events, can contribute to the planning and monitoring of urban and rural areas, at the level of basins and sub-basins. The results facilitate and aid future studies within correlated and multidisciplinary areas.